Pengaruh Leverage, Growth Opportunities, Dan Tax Avoidance Terhadap Cash Holdings (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research was conducted with the aim of knowing the effect of leverage, growth opportunities, and tax avoidance on cash holdings and net working capital as control variables in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange for the period 2017 - 2019. This study uses purposive sampling technique in determining the sample so that the data obtained is 129. The hypothesis was examined using multiple linear regression analysis and processed with Eviews 11 program. From the results of the research that has been done, it can be concluded that leverage has a negative and significant effect on cash holding and growth opportunities have a positive and significant effect on cash holding. However, tax avoidance has no significant effect on cash holding. The implication of this research is that the company must reduce debt and increase the opportunities for future growth because it can affect the level of cash holdings.